(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
This Community Service Program (PKM) aims to empower young farmers in Entabuk Village, Sekadau Regency, through the development of entrepreneurship based on local wisdom derived from the nugal tradition. The nugal tradition is a collective rice-planting practice carried out through cooperation and embodies cultural, social, and ecological values. However, this tradition has gradually been abandoned by younger generations due to modernization and declining interest in the agricultural sector. This program introduces the concept of Nugalpreneur, which integrates local agricultural traditions with entrepreneurial innovation to create sustainable business opportunities. The implementation methods include program socialization, agricultural entrepreneurship training, participatory discussions, and mentoring in the development of business ideas based on local agricultural products. The activities actively involved young farmers as the main subjects of empowerment. The expected outcomes of this program include increased knowledge and skills of young farmers in managing agricultural enterprises, the establishment of a young farmer entrepreneurship community known as “Nugalpreneur” in Entabuk Village, and the creation of innovative business models based on the nugal tradition that generate economic value while contributing to the preservation of local culture. This program is expected to serve as a model for rural community empowerment that integrates cultural values, entrepreneurship, and sustainable development.